Investigating the preferences of older people for telehealth as a new model of health care service delivery: A discrete choice experiment. (February 2017) - Kaambwa, Billingsley; Ratcliffe, Julie; Shulver, Wendy; Killington, Maggie; Taylor, Alan; Crotty, Maria; Carati, Colin; Tieman, Jennifer; Wade, Victoria; Kidd, Michael R
Introduction: Telehealth approaches to health care delivery can potentially improve quality of care and clinical outcomes, reduce mortality and hospital utilisation, and complement conventional treatments. However, substantial research into the potential for integrating telehealth within health care in Australia, particularly in the provision of services relevant to older people, including palliative care, aged care and rehabilitation, is lacking. Furthermore, to date, no discrete choice experiment (DCE) studies internationally have sought the views and preferences of older people about the basic features that should make up a telehealth approach to these services. Methods: Using a DCE, we investigated the relative importance of six salient features of telehealth (what aspects of care are to be pursued during telehealth sessions, distance to the nearest hospital or clinic, clinicians' attitude to telehealth, patients' experience of using technology, what types of assessments should be conducted face-to-face versus via telehealth sessions and the costs associated with receiving telehealth). Data were obtained from an online panel of older people aged 65 years and above, drawn from the Australian general population. Results: The mean age for 330 study participants was 69 years. In general, individuals expressed strong preferences for telehealth services that offered all aspects of care, were relatively inexpensive and targeted specifically at individuals living in remote regions without easy access to a hospital or clinic. Participants also preferred telehealth services to be offered to individuals with some prior experience of using technology, provided by clinicians who were positive about telehealth but wanted all or some pre-telehealth health assessments to take place in a hospital or clinic. Preferences only differed by gender. Additionally, respondents did not feel that telehealth led to loss of privacy and confidentiality. Discussion: Our findings indicate a preference amongst respondents for face-to-face pre-telehealth health assessments and, thereafter, a comprehensive telehealth model (in terms of services offered) targeted at those with some technological know-how as a substitute for attendance at hospitals and clinics, especially where these health facilities were far away from older people's homes. The findings may be usefully incorporated into the design of future telehealth models of service delivery for older people.